The Influence Of Marketing Mix On Purchasing Decisions On Umkm Products Malaysian Chips Reynia - Asyari, Bella Vedia; Yulastri, Asmar; Gusnita, Wiwik; Insan, Ranggi Rahimul (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by the researcher's observation of the marketing mix, which is a marketing strategy carried out to influence consumer purchasing decisions. This study aims to describe the marketing mix, purchasing decisions, and analyze the effect of marketing mix on purchasing decisions on Malaysian Reynia chips MSME products. The research method used in this research is a quantitative method with a causal associative approach. The population in this study were all Malaysian chip MSME customers with an unknown number. The sampling technique used was purposive sampling. Data collection was carried out with a Google form and using a Likert scale that had been tested for reliability validity. Data were analyzed by descriptive and correlation analysis. Based on the results of statistical calculations on marketing mix variables seen from product and price indicators with a percentage of 29%, the most dominant is the consideration of consumers in making purchasing decisions on Malaysian Reynia chips MSME products. The results of the research were conducted using Pearson product moment correlation analysis, it is known that the correlation coefficient of marketing mix (X) with purchasing decisions (Y) is 0.740 which is included in the strong category. The results of the hypothesis test obtained tcount> ttable, namely 8.926> 1.668 and a significance value of 0.000 <0.05. It can be concluded that there is a significant relationship between the marketing mix and purchasing decisions and the hypothesis results are Ha accepted and Ho rejected.